Music listening practices of college-going students and their impact on hearing - H., Gayathri; Paul, Christina Mary P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: A billion youngsters are at risk of recreational noise-induced hearing loss. Motivated by WHO’s campaign ‘Make listening safe’, the objective of this study was to estimate the prevalence of the habit of listening to music at high volumes using Personal Listening Devices (PLDs) among college students and to analyze their audiometric findings. Methods: This cross-sectional study was performed between December 2019 and May 2020 on college-going students with a habit of listening to music using PLDs. PTA was performed on the eligible study subjects. A modified LHQ was given to the selected candidates to answer. Results: The study population comprised 62 boys (24.5%) and 191 girls (75.5%) of the age of 17-24 years. 77.1% of the participants listened to music through PLD, at a scale of >5 on 10 (median PLD volume-7). 26.1% of students listened to music for more than 14 hours a week using their headphones or earphones. Fifteen students (5.93%) had evidence of a 4 kHz dip on PTA out of which 9 patients (3.56%) had bilateral and 6 patients (2.37%) had unilateral involvement. Conclusions: Though many students had some awareness regarding safe volume levels while listening to music, not many were aware of daily sound allowance (DSA). Health education to the target population along with the addition of an in-built app in all PLDs for monitoring device volume and DSA may reduce the impact of music on hearing.